Fish Processing to Increase The Productivity of Raja Ampat's Creative Economy - Siti Nur Azizah; Muhammad Randi Setiadi; Muhammad Randa Setiawan (Universitas Muhammadiyah Purwokerto, 2023)
This research aims to foster the entrepreneurial spirit of homemakers from fishermen's wives in Friwen Village. It is intended to increase family income by innovating and being creative in utilizing local wisdom owned by the village. The methods used in community development are counseling, training, and mentoring. This training involved 30 homemakers and housewives divided into six groups. After counseling and training on another day, evaluating the results of previous counseling and training is helpful. The results of this counseling and training were that the participants gained knowledge and skills in making fish crackers. In addition, there is awareness of the training participants in entrepreneurship by utilizing marine products to increase income, which impacts increasing family welfare. This service value can be developed into a home industry if intensive assistance is carried out with various community development programs.